2018
DOI: 10.1111/jch.13237
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric dimethylarginine levels are associated with augmentation index across naïve untreated patients with different hypertension phenotypes

Abstract: Essential hypertension (EH) represents a major public health problem having an increased incidence of cardiovascular events, mainly stroke and coronary heart disease. Micro-and macrovascular dysfunction contributes to the development of clinically detectable cardiovascular complications in hypertension. Despite a growing body of evidence in the field, the role of vascular dysfunction in the pathophysiology of EH remains under investigation.Recognition of different hypertension phenotypes is currently considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
2
16
1
Order By: Relevance
“…Only seven studies met the inclusion criteria and finally were included in our meta‐analysis (Figure 1). 7,8,16‐20 Most of the studies were conducted in Greece, whereas the other studies were conducted in Brazil, France, and Italy, being published between 2004 and 2019. Only three studies provided arterial stiffness details for all the hypertension phenotypes, 7,8 1 study compared only WCH with normotensives, 16 while one study compared WCH with both normotensives and sustained hypertensives 18 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only seven studies met the inclusion criteria and finally were included in our meta‐analysis (Figure 1). 7,8,16‐20 Most of the studies were conducted in Greece, whereas the other studies were conducted in Brazil, France, and Italy, being published between 2004 and 2019. Only three studies provided arterial stiffness details for all the hypertension phenotypes, 7,8 1 study compared only WCH with normotensives, 16 while one study compared WCH with both normotensives and sustained hypertensives 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Details about the MH population are provided in Table 5. The prevalence of the MH ranges from 6.8% to 21.3%, whereas c‐f PWV results have a wide range from normal to abnormal 7,8,17,19 …”
Section: Resultsmentioning
confidence: 99%
“…[63][64][65] Population-based observational studies reported an inverse relationship between plasma antioxidants and blood pressure, and clinical studies have shown that systolic and diastolic blood pressures correlate positively with biomarkers of oxidative stress (plasma TBARS and 8-epi-isoprostanes) and negatively with antioxidant levels in patients with hypertension. 66,67 Plasma levels of asymmetric dimethylarginine (endothelial NOS inhibitor) and the lipid peroxidation product of linoleic acid, 13-hydroxyoctadecadienoic acid, a marker of ROS production, were inversely correlated with microvascular endothelial dysfunction and elevated blood pressure in hypertensive patients. 68 Endothelial dysfunction, a hallmark of vascular injury in hypertension, is associated with increased vascular ROS production, oxidative stress, and vascular inflammation in patients with hypertension.…”
Section: Evidence Supporting a Role For Ros And Oxidative Stress In Hmentioning
confidence: 99%
“…This negative finding could be explained by small number of untreated patients (n = 20), short treatment duration, and lack of prospective analysis of the subjects. In general population, ADMA levels are independently associated with endothelial dysfunction [36], subclinical arterial damage [7,37,38], and all-cause mortality [12]. ADMA was found to correlate positively with arterial stiffness in adult patients with hypertension (AIx75HR) [37], prediabetes (PWV) [38], and in elderly general population (AIx75HR) [7].…”
Section: Discussionmentioning
confidence: 99%